2014
DOI: 10.1371/journal.pone.0089597
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Premature Ovarian Failure on Mortality and Morbidity among Chinese Women

Abstract: ObjectiveTo evaluate associations of premature ovarian failure (POF) with mortality and morbidity in Asian populations.MethodsWe identified 1,003 cases of POF among 36,402 postmenopausal women who participated in the Shanghai Women's Health Study, a population-based cohort study. Cox regression and logistic regression models were applied in data analysis.ResultsAfter adjustment for potential confounding factors, we found that POF increased the risk of total and cancer-specific mortality (HR (95%CIs): 1.29 (1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 39 publications
1
63
0
2
Order By: Relevance
“…At approximately age 50, female fertility begins to decline along with the continued depletion of the primordial follicle pool until the occurrence of menopause [3]. However, certain pathological conditions, such as endometriosis, myomas, and chemotherapy drugs, are thought to cause premature ovarian failure [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…At approximately age 50, female fertility begins to decline along with the continued depletion of the primordial follicle pool until the occurrence of menopause [3]. However, certain pathological conditions, such as endometriosis, myomas, and chemotherapy drugs, are thought to cause premature ovarian failure [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [39] have shown a decreased risk of breast cancer in POI women. Furthermore, Bösze et al [40] have followed women with POI for 40 years.…”
Section: Follow-up Of Hrt In Adolescents and Young Womenmentioning
confidence: 99%
“…Hormone replacement therapy (HRT) is the most effective way to treat the immediate symptoms of estrogen deficiency and prevent long‐term sequelae. For most women experiencing an early or premature menopause, HRT presents minimal risks and there are very few absolute contraindications to its use …”
Section: Introductionmentioning
confidence: 99%